Consumer protection under hire-purchase law in Malaysia / Adli Abdul Ghalib - Abdul Ghalib, Adli (Faculty of Law, 1985)
Hire-Purchase trading first started in England in 1846 When Mr. Henry Moore, the Bishopsgate piano maker, introduced it in that year. However, it was only in the second half of the nineteenth centruy that hire-purchase finds its place in the commercial sphere when the Singer Manufacturing Company began to offer housewives and others the opportunity of acquiring sewing machines on "hire and purchase" terms. Thus, the precedent was sax. Vendors of furniture, piano and other household consumer goods followed suit. At about the same time, in the industrial sphere, North Central and British Wagon Companies began to finance the purchase of railway wagons by collieries needed for the carriage o f " coal, and security for the advances made was provided by hire-purchase agreements. Unlike the Singer Company, the wagon companies were not themselves primarly engaged in the manufacture or sale of goods let on hire. They were, in fact, the first examples of finance companies which today form an integral partin hire-purchase transactions. With the invention of automobiles, the ambit of hire-purchase had been extended to a large extent, and now, we have a wide range of consumer goods to choose from.